1997
DOI: 10.1016/s1074-7613(00)80388-x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 3-Kinase Couples the Interleukin-2 Receptor to the Cell Cycle Regulator E2F

Abstract: Cell cycle progression initiated by interleukin-2 (IL-2) in T cells is critical for lymphoproliferation and an immune response. Phosphatidyl inositol 3-kinase (PI3K) is activated by IL-2. However, nuclear targets for PI3K are not known. Here we identify the cell cycle regulator E2F as an IL-2 target in T lymphocytes and PI3K as the critical signaling pathway. We eliminate both Stat5 and Raf/MEK pathways from E2F regulation. Protein kinase B (PKB) is activated by IL-2 via PI3K. The expression of an active PKB i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
317
0
1

Year Published

1998
1998
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(345 citation statements)
references
References 61 publications
26
317
0
1
Order By: Relevance
“…The downstream e ectors of the PI 3-kinase involved in the G1-S progression in Ba/F3 cells are not known. One candidate could be the cell cycle regulator E2F which has been shown to be a target of PI 3-kinase in T-cells (Brennan et al, 1997). Expression of proteins involved in G1-S transition like cyclins D, cyclin dependent kinases and inhibitors of cycline dependent kinases will require also careful analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The downstream e ectors of the PI 3-kinase involved in the G1-S progression in Ba/F3 cells are not known. One candidate could be the cell cycle regulator E2F which has been shown to be a target of PI 3-kinase in T-cells (Brennan et al, 1997). Expression of proteins involved in G1-S transition like cyclins D, cyclin dependent kinases and inhibitors of cycline dependent kinases will require also careful analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the proliferative advantage of HTLV-I-transformed Tcells may be related to the maintenance of limiting amount of p27 Kip1 , as also suggested by the ®nding that the amount of p27 Kip1 is lower in transformed than immortalized T-cells. It has been shown that IL-2 decreases the stability of p27 Kip1 by increasing its proteolysis (Pagano et al, 1995); this event is presumably mediated by PI3K phosphorylation activity (Brennan et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…A recent report suggests that the regulation of p27 Kip1 expression by IL-2 occurs through the activity of P13K (Brennan et al, 1997). To investigate whether the decreased amount of p27 Kip1 observed in HTLV-Itransformed T-cells results from the constitutive activation of P13K, three IL-2-dependent and four IL-2-independent HTLV-I-infected T-cell lines and PHA-PBMC were treated with the speci®c inhibitor of P13K, LY294002, and analysed 24 h later for p27 Kip1 expression and DNA content.…”
Section: P13k Inhibition Is Associated With Upregulation Of P27 Kip1 mentioning
confidence: 99%
“…To further con®rm the involvement of these pathways, we carried out Elk-1 transactivation studies with dominant negative constructs of Raf-1 and the p85 subunit of PI3 kinase (Bruder et al, 1992;Brennan et al, 1997). These constructs did not only abrogate the DHT e ect but they also reduced the basal activity which possibly arose as a result of residual hormone in the culture medium (Figure 5a).…”
Section: Sensitivity To Kinase Inhibitorsmentioning
confidence: 99%